PELATIHAN PEMBUATAN PUPUK KOMPOS BERBAHAN ECENG GONDOK DI DESA KUALA BA’U KECAMATAN KLUET UTARA - Safridatul 'Audah; Meraty Ramadhini; Bakruddin; Devi Satria Saputra; Afdhal; Herry Setiawan; Hasbaini (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
ABSTRACT The enclosure of the Krueng Matee waters by vegetation can threaten the preservation of underwater biota, such as fish and shrimp due to lack of oxygen and sunlight, thus the water hyacinth plants reproduce as weeds in the waters of the Krueng Matee river, Kuala Ba'U Village and affect the livelihoods of Kuala Ba'U fishermen. One of the efforts that can be made to overcome water hyacinth weeds is to utilize water hyacinth plants for compost. This community service activity aimed to provide skills in processing water hyacinth into compost for the people of Kuala Ba'U Village. The stages in implementing this activity consisted of field observations, carrying out village administration, the Participatory Action Research (PAR) method, preparation of materials and a multipurpose counter machine. The result of this community service was the availability of compost from water hyacinth as well as a good response and welcome from the community and community leaders of Kuala Ba'U Village because the community gained knowledge and skills in processing water hyacinth into compost, thereby reducing water pollution and improving the community's economy, especially for farmers. In addition, this activity can also normalize the estuary of the Krueng Matee river from water hyacinth weeds, so fishermen can return to fishing and catching fish.